2011
DOI: 10.1128/jb.05362-11
|View full text |Cite
|
Sign up to set email alerts
|

The σ B -Dependent yabJ-spoVG Operon Is Involved in the Regulation of Extracellular Nuclease, Lipase, and Protease Expression in Staphylococcus aureus

Abstract: The alternative sigma factor B of Staphylococcus aureus is involved in the coordination of the general stress response, expression of virulence determinants, and modulation of antibiotic resistance levels. It controls a large regulon, either directly by recognizing conserved B promoter sequences or indirectly via B -dependent elements. The B -controlled yabJ-spoVG operon encodes two such putative downstream elements. We report here transcriptome analysis in S. aureus Newman, showing that inactivation of the ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…It was also reported that SigB prevents biofilm dispersion by repressing nuclease activity [40], which is a mechanism we also observed in the SCV CF07-S. Studying the molecular mechanisms controlling extracellular nuclease activity in SCVs should be of interest as SigB was also described to activate nuc1 expression through the SpoVG-dependent pathway [49]. Overall, SigB positively controls biofilm formation by at least two different mechanisms in the SCV CF07-S: it supports the expression of fnbA and represses nuclease activity.…”
Section: Discussionsupporting
confidence: 68%
“…It was also reported that SigB prevents biofilm dispersion by repressing nuclease activity [40], which is a mechanism we also observed in the SCV CF07-S. Studying the molecular mechanisms controlling extracellular nuclease activity in SCVs should be of interest as SigB was also described to activate nuc1 expression through the SpoVG-dependent pathway [49]. Overall, SigB positively controls biofilm formation by at least two different mechanisms in the SCV CF07-S: it supports the expression of fnbA and represses nuclease activity.…”
Section: Discussionsupporting
confidence: 68%
“…The spoVG gene encodes for the downstream modulator SpoVG of the σ B general stress response (Schulthess et al, 2011), rsbU encodes for the RsbU activator of σ B (Hecker et al, 2007), while rpoF encodes for the alternative sigma factor SigB (σ B ) (Hecker et al, 2007). None of the seven sequenced lineages evolved with gentamicin had acquired mutations related to the σ B stress response.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have also found that spoVG deletion can reduce oxacillin resistance in MRSA strain N315. SpoVG can directly regulate fmtB, which is one of the fem or aux genes (26,28). It has been reported that femA, also one of fem or aux genes, is involved in the synthesis of pentaglycin cross-links (5).…”
Section: Discussionmentioning
confidence: 99%
“…In nonsporulating bacteria, the B -controlled spoVG affects capsule synthesis, expression of virulence factors, and antibiotic resistance (25)(26)(27). SpoVG is considered a site-specific DNA-binding protein (28).…”
mentioning
confidence: 99%